Type I Clathrates as Novel Silicon Anodes: An Electrochemical and Structural Investigation. Issue 6 (5th May 2015) - Li, Ying; Raghavan, Rahul; Wagner, Nicholas A.; Davidowski, Stephen K.; Baggetto, Loïc; Zhao, Ran; Cheng, Qian; Yarger, Jeffery L.; Veith, Gabriel M.; Ellis‐Terrell, Carol; Miller, Michael A.; Chan, Kwai S.; et al.
<x xml:space="preserve">Abstract</x> Silicon clathrates contain cage‐like structures that can encapsulate various guest atoms or molecules. An electrochemical evaluation of type I silicon clathrates based on Ba8AlySi46−y as the anode material for lithium‐ion batteries is presented here. Postcycling characterization with nuclear magnetic resonance and X‐ray diffraction shows no discernible structural or volume changes even after electrochemical insertion of 44 Li (≈1 Li/Si) into the clathrate structure. The observed properties are in stark contrast with lithiation of other silicon anodes, which become amorphous and suffer from large volume changes. The electrochemical reactions are proposed to occur as single phase reactions at approximately 0.2 and 0.4 V versus Li/Li+ during lithiation and delithiation, respectively, distinct from diamond cubic or amorphous silicon anodes. Reversible capacities as high as 499 mAh g−1 at a 5 mA g−1 rate were observed for silicon clathrate with composition Ba8Al8.54Si37.46, corresponding to ≈1.18 Li/Si. These results show that silicon clathrates could be promising durable anodes for lithium‐ion batteries.